Improving Mental Health Through the Regeneration of Deprived Neighborhoods: A Natural Experiment - White, James (Am J Epidemiol, 2017)
Neighborhood-level interventions provide an opportunity to better understand the impact of neighborhoods on health. In 2001, the Welsh Government, United Kingdom, funded Communities First, a program of neighborhood regeneration delivered to the 100 most deprived of the 881 electoral wards in Wales. In this study, we examined the association between neighborhood regeneration and mental health. Information on regeneration activities in 35 intervention areas (n = 4,197 subjects) and 75 control areas (n = 6,695 subjects) was linked to data on mental health from a cohort study with assessments made in 2001 (before regeneration) and 2008 (after regeneration). Propensity score matching was used to estimate the change in mental health in intervention neighborhoods versus control neighborhoods. Baseline differences between intervention and control areas were of similar magnitude as produced by paired randomization of neighborhoods. Regeneration was associated with an improvement in the mental health of residents in intervention areas compared with control neighborhoods (β = 1.54, 95% confidence interval: 0.50, 2.59), suggesting a reduction in socioeconomic inequalities in mental health. There was a dose-response relationship between length of residence in regeneration neighborhoods and improvements in mental health (P-trend = 0.05). These results show that targeted regeneration of deprived neighborhoods can improve mental health.